Navigating AI in Central Asia: Legal Systems, Free Economic Zones, and Global Partnerships - Wang, Shumin; Maysa, Odenyazova; Bashir Dar, Saira; Saeed, Anwar; Novikova, Kseniia (International Journal of Social Sciences and Public Administration, 2025)
The study examines the integration of artificial intelligence (AI) and its regulatory frameworks in the context of Central Asian countries in Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan as these countries drive their economic and technological development. The main objectives of this study will be to analyze and compare normative acts, strategies of the inherent states and policy documents, to reveal how effective regulation and AI governance can facilitate the regional development, how governance systems of regulation can enable the AI to develop rapidly, and how regional zones of innovation will promote the economic growth and development of the infrastructure of countries of the region as well as the competitiveness of the technology. Another objective is to show that the sectors of innovations will promote AI startups, foster their development, and strengthen international connections to build innovation ecosystems. Drawing on China’s expertise in AI governance system reveals opportunities where collaboration with the other parties could enliven the digital economy of the Central Asia region, create jobs and new opportunities in the health care and education sectors. This study illustrates how important adaptive regulatory frameworks are to facilitate AI and support economic development. It encourages the rapid adoption of targeted normative act for the AI systems and investment in AI education and training to address the lack of expertise so that the technological benefits are widely available. By analyzing the interplay between regulation, innovation zones, and international partnerships, this study provides valuable observations and policy recommendations to support decision-making on effective practices of regulatory strategies for the field of AI system to sustainable economic and technological growth.